Handheld calculators as tools for students’ learning of algebra - Persson, Per-Eskil (NOMAD Nordic Studies in Mathematics Education, 2009)
What evidence can be found in recent research literature of the potential positive or negative effects of using graphic calculators (GC) and symbolic calculators (CAS) in mathematics education? The focus of this literature review is the use of handheld calculators and their effect on algebra learning, with theoretical backgrounds for the use of this type of technology in classroom practice. Special attention is given to three areas: students’ conceptions of literal symbols and of algebraic expressions, fundamental for their ability to work with algebra; functional and modelling approaches, both important for students’ view of algebra as a useful tool in problem solving; and approaches within CAS, which put special demands for changes in educational methods. Results of some recent meta-studies, based on a relatively large number of research papers and reports, are also discussed, as well as the importance of students’ and teacher’s beliefs. Common results are compiled and synthesised for a formulation of some important implications for teaching and pre-service teacher education.